ANALISIS PROSEDUR PERTANGGUNGJAWABAN BENDAHARA PENGELUARAN PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN TIMOR TENGAH SELATAN - Melyanus J. Selan; Thobias E. D. Tomasowa; Deetje W. Manuain (P3M- Politeknik Negeri Kupang, 2019)
This study aims to determine the procedure for the treasurer's accountability for spending at the Public Works Department and the Spatial Planning District. TTS based on Permendagri No. 13 of 2006 and Permendagri No, 55 of 2008. The analytical method used is descriptive qualitative method, a method that emphasizes the aspects of understanding in depth to a problem.The object of this study is the Financial Administration Officer (PPK), the Technical Implementation Activity Officer (PPTK), the Treasurer of Expenditures and the Treasurer of Assistant Expenditures at the PUPR Service District. TTS. Data obtained by interview and documentation of the object of research.The results of this study indicate that: (1) Treasurer of the Public Works Expenditures of PUPR Kab. TTS has carried out financial accountability procedures in accordance with applicable guidelines, from SP2D disbursement, collection of transaction evidence, bookkeeping to the stage of ratification and submission of reports to related parties; (2) There are 5 (five) factors that become a classic problem in the timeliness of the submission of the accountability report so that it needs to be taken seriously so that it is no longer an obstacle in the submission of the treasurer accountability report.